2014
DOI: 10.1186/2050-7771-2-6
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter phase II clinical trial of nilotinib for patients with imatinib-resistant or -intolerant chronic myeloid leukemia from the East Japan CML study group evaluation of molecular response and the efficacy and safety of nilotinib

Abstract: BackgroundNilotinib is a second-generation tyrosine kinase inhibitor that exhibits significant efficacy as first- or second-line treatment in patients with chronic myeloid leukemia (CML). We conducted a multicenter Phase II Clinical Trial to evaluate the safety and efficacy of nilotinib among Japanese patients with imatinib-resistant or -intolerant CML-chronic phase (CP) or accelerated phase (AP).ResultsWe analyzed 49 patients (33 imatinib-resistant and 16 imatinib-intolerant) treated with nilotinib 400 mg twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Several reports have demonstrated that BCR-ABL Ins35bp is detected mainly in patients who have achieved hematological/cytogenetic response, but not DMR, despite long-term TKI treatment. (6,12,15,43) In contrast, extremely low amounts of BCR-ABL Ins35bp were detected in patients with newly-diagnosed, previously untreated CML (data not shown). We found that TKI treatment inhibits recruitment of RNA polymerase a toward genomic BCR-ABL, which positively regulates both transcription and pre-mRNA intron splicing, resulting in a relative increase in the amount of BCR-ABL Ins35bp with a decrease of total BCR-ABL transcript level.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Several reports have demonstrated that BCR-ABL Ins35bp is detected mainly in patients who have achieved hematological/cytogenetic response, but not DMR, despite long-term TKI treatment. (6,12,15,43) In contrast, extremely low amounts of BCR-ABL Ins35bp were detected in patients with newly-diagnosed, previously untreated CML (data not shown). We found that TKI treatment inhibits recruitment of RNA polymerase a toward genomic BCR-ABL, which positively regulates both transcription and pre-mRNA intron splicing, resulting in a relative increase in the amount of BCR-ABL Ins35bp with a decrease of total BCR-ABL transcript level.…”
Section: Discussionmentioning
confidence: 88%
“…It has remained unclear how alternatively spliced BCR‐ABL Ins35bp variants can be acquired in CML cells under TKI treatment, and why mis‐splicing reproducibly occurs at the specific sites of intronic 35 bp in ABL intron 8. Several reports have demonstrated that BCR‐ABL Ins35bp is detected mainly in patients who have achieved hematological/cytogenetic response, but not DMR, despite long‐term TKI treatment . In contrast, extremely low amounts of BCR‐ABL Ins35bp were detected in patients with newly‐diagnosed, previously untreated CML (data not shown).…”
Section: Discussionmentioning
confidence: 89%
“…The threshold for nilotinib C 0 should be set above 761 ng/mL on a receiver operating characteristic (ROC) curve with a sensitivity of 76.2% and specificity of 77.8%. 60) Afterwards, however, 10 patients during the first 12 months discontinued nilotinib treatment because of severe adverse events such as thrombocytopenia and hyperbilirubinemia. 61) Consequently, in the final analysis of the EJCML study, the nilotinib C 0 tended to increase in patients who achieved MMR at 12 months, but this result was not statistically significant; the median C 0 were 774 ng/mL and 490 ng/mL (less than 500 ng/mL), respectively (p=0.261).…”
Section: Nilotinib Tdmmentioning
confidence: 99%
“…On the other hand, in UGT1A1 EM patients who achieved MMR at 12 months, the steady-state mean nilotinib C 0 was 934 ng/ mL. 59) Based on the EJCML study and the steady-state mean nilotinib C 0 , 59,61) a target C 0 of 800 ng/mL is recommended for TDM after administration of the initial 600 mg/d dose of nilotinib (Fig. 4).…”
Section: Nilotinib Tdmmentioning
confidence: 99%
“…A target C trough of 761 ng/mL is recommended for nilotinib TDM. 108 Pazopanib. Clinical studies [109][110][111][112] have established a target C trough of 20 000 ng/mL for pazopanib.…”
Section: Additional Tkis Potentially Feasible For Tdmmentioning
confidence: 99%